REVITALISASI BANGUNAN TRADISIONAL RUMAH TINGGAL SEBAGAI HOMESTAY DENGAN PENDEKATAN ADAPTIVE REUSE DI JAGALAN, KOTAGEDE, YOGYAKARTA - SIsca Pramudya Wardani; Ana Hardiana; Fauzan Ali Ikhsan (Universitas Sebelas Maret Surakarta, 2016)
The sustainability for cultural heritage is a vital thing for present time and future. Recently, traditional house which is a javanese cultural heritage is slowly gone in Jagalan, Kotagede. Homestay in jagalan kotagede as a living museum which has a characteristic of cultural properties area has changed. The change is because of the necessity of a modern living which can not adapt to the old culture, economic necessity, and also eathquake in Jogja in 2006 go along the dull of Jagalan, Kotagede area characteristics. As Jagalan characteristics seems arousing little interest, it makes Jagalan loses heritage spirit and also leads to the unorganized local people. These are due to the economical, social and political matters. Thus, the effort to achieve harmony will be done, including area planning, traditional home stay building, local art, culinary road characteristics, Jagalan potential and adaptive side to the earthquake effect. The official announcement of “Jagalan Tlisih” by Sultan Hamengku Buwono X will be able to make everyone realize that the sustainability of cultural heritage is important. Jagalan Village should be supported by maintaining the potential within, in order to accomplish the realization of cultural tourism village. moreover, traditional building which is counted as potential legacy needs to be preserved and maintained. The maintenance is by revitalizing, to revive and to restore. Adaptive concepts is a way to build an object and environment so that when these aspects are combined they will be able to work together and create new thing without losing identity of their own. The preservation is applied by taking advantage from the traditional house to be a homestay. Moreover, homestay will be a new function in the form of traditional building to support Jagalan Village which has heritage value to fulfill the goal as a tourism destination. Furthermore, Jagalan area will be local based homestay along with adaptive people within its function as cultural tourism village. The new function is one of Adaptive Reuse as a dynamic revitalization responses from spatial, physic, and style aspect which can stands alone and revive its environment.